Usefulness of laparoscopic cholecystostomy in children with complicated choledochal cyst. Issue 2 (11th February 2015) - Yamoto, Masaya; Urushihara, Naoto; Fukumoto, Koji; Miyano, Go; Nouso, Hiroshi; Morita, Keiichi; Miyake, Hiromu; Kaneshiro, Masakatsu; Koyama, Mariko
Abstract: Introduction: In children with choledochal cysts (CC), obstruction of the discharge of bile or pancreatic juice is frequently observed, and biliary perforation and severe pancreatitis may occur. In such cases, temporary drainage is necessary to stabilize these patients. We employed laparoscopic cholecystostomy followed by laparoscopic cyst excision in cases with complicated CC. Methods: Between 2009 and 2013, emergency laparoscopic cholecystostomy for bile drainage was performed in seven girls with complicated CC in whom conservative treatment failed to ameliorate abdominal pain, vomiting, and jaundice; among these seven patients included two with biliary perforation, one with a huge cyst, and four with peribiliary edema suggestive of impending biliary rupture. Protein plugs in the common channel or the terminal portion of the cyst were present in six patients. Results: Amelioration of symptoms, such as abdominal pain and jaundice, was achieved in all patients after laparoscopic cholecystostomy. Saline irrigation of the bile duct via cholecystostomy was commenced 2 days postoperatively. All patients underwent laparoscopic cyst resection after improvement of their general condition and detailed evaluation of the intrahepatic and extrahepatic bile ducts and pancreaticobiliary maljunction. Impacted protein plugs or gallstones were eliminated in all patients by the time of laparoscopic cyst excision. Conclusion: Laparoscopic cholecystostomy followed by laparoscopic cyst excision is a useful and safe procedure for the treatment of complicated CC. This technique is also favorable from a cosmetic viewpoint because the resultant wound can be reused as the trocar insertion site at the time of laparoscopic cyst excision.